Stealthing Perpetration and Victimization: Prevalence and Correlates Among Emerging Adults - Bonar, Erin E. (Journal of interpersonal violence, 2021)
“Stealthing” is a form of sexual violence wherein a sexual partner purposefully removes a condom during penetration without the receptive partner’s knowledge. Given the role of substance use in sexual violence broadly, we examined demographic and substance use correlates of stealthing perpetration (SP) and victimization (SV) among emerging adults. Participants comprised 2,550 18- to 25-year-olds (M age = 20.8, SD = 2.3), recruited via social media (48% female; 53.9% non-Hispanic White; 46.0% had another racial/ethnic identity; 67.4% heterosexual; 85.3% had some college education). Unadjusted analyses (t tests, χ2 analysis) and adjusted logistic regression analyses examined associations between demographics (age, education, race/ethnicity, sexual orientation) and substance use (binge drinking, marijuana use, other illegal drug use, and prescription drug misuse) with male SP and male and female SV. Five percent of males and 18.9% of females reported SV; 6.1% of males reported SP. In adjusted analyses, significant correlates of SP were: non-Hispanic White race/ethnicity (odds ratio [OR] = 0.39), binge drinking (OR = 1.39), cannabis use (OR = 1.37), and other drug use (OR = 1.43). Significant correlates of male SV were: non-Hispanic White race/ethnicity (OR = 0.28), non-heterosexual orientation (OR = 0.24), binge drinking (OR = 1.49), and other illegal drug use (OR = 1.79). Significant correlates of female SV were: older age (OR = 1.13), non-Hispanic White race/ethnicity (OR = 0.57), binge drinking (OR = 1.28), cannabis use (OR = 1.29), and other drug use (OR = 1.22). Consistent with literature linking alcohol to sexual violence, binge drinking correlated with both SV and SP, with other substance use also playing a role. Data are needed to explore these relationships using longitudinal, event-level assessments to investigate the influence of acute intoxication. Interventions to reduce sexually transmitted infections, unintended pregnancy, and sexual assault should include content on stealthing and substance use.